Rapid complete atrioventricular heart block reversal due to Lyme carditis - Khalil I. Bourji; T. Newsome; John Meyerhoff (Greater Baltimore Medical Center, 2018)
A 49-year-old man, who presented with new onset dyspnea on exertion and fatigue without clear history of a typical erythema migrans rash, was found to have complete atrioventricular (AV) heart block with positive serology for Lyme disease. A complete stepwise reversal of the AV block was achieved shortly after the initiation of intravenous antibiotic treatment.